The Utility of Preoperative Vascular Grading in Patients Undergoing Surgery First for Pancreatic Cancer: Does Radiologic Arterial or Venous Involvement Predict Pathologic Margin Status?. (13th August 2018) - Goel, Neha; D'Souza, Jimson W.; Ruth, Karen J.; Milestone, Barton; Karachristos, Andreas; Nagarathinam, Rajeswari; Cooper, Harry; Hoffman, John; Reddy, Sanjay
Abstract : Controversy exists on accurately grading vascular involvement on preoperative imaging for pancreatic ductal adenocarcinoma. We reviewed the association between preoperative imaging and margin status in 137 patients. Radiologists graded venous involvement based on the Ishikawa classification system and arterial involvement based on preoperative imaging. For patients with both classifications recorded, we categorized vascular involvement as "None, " "Arterial only, " "Venous only, " or "Both" and examined the association of vascular involvement and pathologic margin status. Of 134 patients with Ishikawa classifications, 63%, 17%, 11%, and 9% were graded as I, II, III, and IV, respectively. Of 96 patients with arterial staging, 74%, 16%, and 10% were categorized as stages i, ii, and iii, respectively. Of 93 patients with both stagings, 61% had no vascular involvement, 7% had arterial only, 14% had venous only, and 17% had both involved. Ishikawa classification was strongly associated with a positive SMA and SMV margin (p<0.001). However, for arterial staging, there was no association with SMA or SMV margin. Overall, Ishikawa grading was more predicative of arterial involvement and remained significant on multivariate analysis. The use of diagnostic imaging in predicting positive margins is more accurate when using a venous grading system.